Enhancing Consumers' Affection for a Brand Using Product Design. Issue 5 (8th October 2014) - Kumar, Minu; Townsend, Janell D.; Vorhies, Douglas W.
<x xml:space="preserve">Abstract</x> Product design is an integral component of a brand and an important driver of brand equity. For the brand, product design is an important tool for driving differentiation, creating value for both the consumer and the firm, driving consumer preferences, and creating a sustainable competitive advantage. At the firm level, the importance of investing in design has been substantiated by studies that suggest firms capable of creating innovative design and providing superior consumer value perform better in the marketplace. Thus, product design clearly presents an important area of research for those studying and managing brands. In this context, the goal of this research is to explain the brand‐level affective outcomes that product‐level design features can create. This paper develops a conceptual framework and hypotheses that theoretically connect design‐based values, at the product level, to affective brand‐level relational outcomes with the brand. The drivers of product affection include social value, altruistic value, functional value, emotional value, and economic value. Analogous to "firm affection, " the paper postulates a brand affection construct that is defined as the passion and pride that a consumer feels about owning a brand. Using syndicated product‐level data from the automotive industry collected from a national sample of consumers, 712 useable consumer/product observations of 30 small vehicles are employed in the analysis. A confirmatory factor analysis and structural equation model are developed to test the conceptual model. This research finds that the social value and emotional value that a design provides to consumers have a greater effect on brand affection than purely transactional values, such as functional value or economic value. This research contributes to the literature by providing evidence that product design‐related values are multifaceted and can contribute to relational outcomes, such as brand affection. It contributes to practice by highlighting the means by which design can be used as a strategic tool to create a sustainable long‐lasting relationship with the consumer, and provides managers with a framework to assess the impact of design‐based values on long‐term relationship‐based outcomes. The results provide new insights about how consumers' perceptions of the value of product design at the product level can help create enduring relationships with brands.